INDONESIA AIRLINES' COMPETITIVE STRATEGIES - Ahmad Gozali (Universitas Pamulang, 2022)
The more open the global economy, the increasing use of airlines, at the same time tightening competition, both domestic and international flights. Therefore, this study seeks to see and analyze the airline's marketing strategy from the perspective of flight service quality and price penetration. To test the research data, used quantitative methods with regression analysis techniques. This is to see the possible cause and effect of a variable, so that the effectiveness of the implemented strategy is known. The object of this research is Citilink airline users, using accidental sampling technique. The results showed that statistically there was a causal relationship that was linear. Where there is an increase in the use of airlines when there is an increase in service and price promotions. This confirms that if the airline's competitive strategy is through strengthening services and competitive prices, it can strengthen the airline's competitive position.Keywords: Competitive Strategy, Service Quality, Price Penetration, Consumer Decision